1982
DOI: 10.1007/bf00218284
|View full text |Cite
|
Sign up to set email alerts
|

A comparative ultrastructural and physiological study on melanophores of wild-type and periodic albino mutants of Xenopus laevis

Abstract: Pigment of tail-fin melanophores in periodic albino Xenopus laevis tadpoles is dispersed in response to darkness and to alpha-MSH in a manner similar to wild-type melanophores. However, periodic albino tadpoles lack the response to different background conditions and the melatonin-induced aggregation in darkness. The tyrosinase activity in cells of the latter type tadpoles is weak compared to the wild-type cells. Ultrastructural examination of melanophores from periodic albino mutants and cells from wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The culture of mutant melanophores made previously to clarify the mechanism of depigmentation during larval development revealed that they depigment gradually during proliferation in vitro, and that the depigmented cells are filled with premelanosomes with typical lamellar structures instead of a p ‐type melanosomes (8). Similar observations were obtained by ultrastructural studies on these mutant melanophores (stages 50–54) (9). It was further shown that not only melanophores but also iridophores are affected in the periodic albino (10), and that reflecting platelets in mutant iridophores are abnormal in size and shape (11).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…The culture of mutant melanophores made previously to clarify the mechanism of depigmentation during larval development revealed that they depigment gradually during proliferation in vitro, and that the depigmented cells are filled with premelanosomes with typical lamellar structures instead of a p ‐type melanosomes (8). Similar observations were obtained by ultrastructural studies on these mutant melanophores (stages 50–54) (9). It was further shown that not only melanophores but also iridophores are affected in the periodic albino (10), and that reflecting platelets in mutant iridophores are abnormal in size and shape (11).…”
Section: Introductionsupporting
confidence: 86%
“…This result can be explained by the effect of α MSH on pigment cells, since the expression of iridophores is stimulated in the environment where α MSH is absent or scarce (28). A possibility has been proposed that insufficient α MSH may cause the pale color of periodic albino mutant of X. laevis (9), however, a contradictory result has been shown that parabiosis of wild‐type and periodic albino mutant embryos does not affect the differentiation of the pigment pattern of either animal (33). Factor(s) other than α MSH may affect the expression of pigment cells in the periodic albino mutant.…”
Section: Discussionmentioning
confidence: 99%
“…This mutant is characterized by the absence of melanin in oocytes, the appearance of melanin in the pigment epithelium of the eye and in skin melanophores at larval stages, and the almost complete disappearance of melanin in metamorphosed animals (Hoperskaya 1975). Ultrastructural observation has revealed that melanophores in this mutant contain many abnormal melanosomes with granular internal structures (Fukuzawa and Ide 1986; Hoperskaya 1981; Seldenrijk et al 1982). It has been shown that iridophores (Fukuzawa 2006; MacMillan 1979; MacMillan and Gordon 1981) and xanthophores (Fukuzawa 2006) are also affected in the periodic albino.…”
Section: Introductionmentioning
confidence: 99%
“…Albinism is widespread in the animal kingdom, and is caused by the absence of melanocytes or melanin in the integument (Arthur et al, 2005;Nolan and Robert, 1990;Seldenrijk et al, 1982;Spritz et al, 2003;Wang et al, 2007). For example, the melanocytes in the skin of larval albino turbots (Scophthalmus maximu) contain fewer melanosomes, while the adults do not have melanocytes (Guo et al, 2007).…”
Section: Introductionmentioning
confidence: 96%